1995
DOI: 10.1074/jbc.270.30.17962
|View full text |Cite
|
Sign up to set email alerts
|

CCAAT/Enhancer-binding Protein Isoforms γ and δ Are Expressed in Mammary Epithelial Cells and Bind to Multiple Sites in the β-Casein Gene Promoter

Abstract: Lactogenic hormone-dependent expression of the rat beta-casein gene in mammary epithelial cells is controlled via a complex regulatory region in the promoter. The sequence between -176 and -82 is the minimal region to confer the response to glucocorticoid hormone and prolactin on a heterologous promoter. The response is further enhanced by the region between -282 and -176. DNase I footprinting experiments and electromobility shift assays revealed the presence of four binding sites for CCAAT/enhancer-binding pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
54
0

Year Published

1997
1997
2005
2005

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(60 citation statements)
references
References 61 publications
6
54
0
Order By: Relevance
“…6 and 8). The ␤-casein promoter has several binding sites for the CCAAT-enhancer binding protein (C/EBP) (38), and the isoforms C/EBP␤ and -␦ reportedly bind to these sites to increase expression during pregnancy (10). C/EBP␤ has been shown to control the proliferation and differentiation of mam-VOL.…”
Section: Discussionmentioning
confidence: 99%
“…6 and 8). The ␤-casein promoter has several binding sites for the CCAAT-enhancer binding protein (C/EBP) (38), and the isoforms C/EBP␤ and -␦ reportedly bind to these sites to increase expression during pregnancy (10). C/EBP␤ has been shown to control the proliferation and differentiation of mam-VOL.…”
Section: Discussionmentioning
confidence: 99%
“…Extensive studies have defined multiple cis-acting elements and transcription factors involved in the regulation of milk protein production. These include binding sites for the glucocorticoid receptor (2), signal transducers and activators of transcription (3,4), CAAT/enhancer-binding protein (5), and nuclear factor 1 (NF1) 1 (4). In a previous paper (6), we demonstrated that a member(s) of the NF1 family plays an important role in the expression of the milk protein gene carboxyl ester lipase (CEL).…”
mentioning
confidence: 99%
“…STAT5 binding sites are found in many other milk protein promoters, with the STAT binding sites in the sheep ␤-lactoglobulin gene being particularly well characterized (5,6,51,58). C/EBP binding sites are required for the hormonal induction of ␤-casein expression (16,41,49), and its activity may be influenced by glucocorticoid receptor, which has been shown to enhance prolactin-induced expression of ␤-casein (15,25,41,44,50).…”
mentioning
confidence: 99%